Neurological update: use of cardiac troponin in patients with stroke - Scheitz, Jan F.; Stengl, Helena; Nolte, Christian H.; Landmesser, Ulf; Endres, Matthias (Journal of neurology, 2021)
Cardiac troponin is a specific and sensitive biomarker to identify and quantify myocardial injury. Myocardial injury is frequently detected after acute ischemic stroke and strongly associated with unfavorable outcomes. Concomitant acute coronary syndrome is only one of several possible differential diagnoses that may cause elevation of cardiac troponin after stroke. As a result, there are uncertainties regarding the correct interpretation and optimal management of stroke patients with myocardial injury in clinical practice. Elevation of cardiac troponin may occur as part of a ‘Stroke-Heart Syndrome’. The term ‘Stroke-Heart Syndrome’ subsumes a clinical spectrum of cardiac complications after stroke including cardiac injury, dysfunction, and arrhythmia which may relate to disturbances of autonomic function and the brain–heart axis. In this review, we provide an up-to-date overview about prognostic implications, mechanisms, and management of elevated cardiac troponin levels in patients with acute ischemic stroke.